Positive listing regulation systems in the wildlife trade: policy recommendation - Parga, Ava, author; Vieira, Nicole, advisor; Sloan, Daniel, committee member (Colorado State University. Libraries, 2025)
This paper is intended to thoroughly explain the mechanisms through which the wildlife trade threatens biodiversity, and how positive listing regulations alleviate these threats relative to negative listing regulations. Negative listing regulation systems only include regulations against, or limitations of, the trade of certain species. By contrast, positive listing regulation systems regulate the trade by only permitting the trade of certain species explicitly written into law. Ultimately, a legislative implementation of positive listing regulation systems in the United States of America is recommended.